2023
DOI: 10.1111/dme.15232
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost‐effectiveness of intermittently scanned continuous glucose monitoring in adults with type 1 diabetes in England

Rachel A. Elliott,
Gabriel Rogers,
Mark L. Evans
et al.

Abstract: ObjectiveWe previously showed that intermittently scanned continuous glucose monitoring (isCGM) reduces HbA1c at 24 weeks compared with self‐monitoring of blood glucose with finger pricking (SMBG) in adults with type 1 diabetes and high HbA1c levels (58–97 mmol/mol [7.5%–11%]). We aim to assess the economic impact of isCGM compared with SMBG.MethodsParticipant‐level baseline and follow‐up health status (EQ‐5D‐5L) and within‐trial healthcare resource‐use data were collected. Quality‐adjusted life‐years (QALYs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a recently published study on the cost-effectiveness of telemedicine interventions, smartphone app, SMS text messaging, and website interventions were confirmed to be cost-effective without substantial differences among the different delivery modes [ 70 ]. A study by Elliott et al [ 71 ] showed that smart wearable devices increase short-term costs but their HbA 1c -lowering benefits will provide sufficient long-term health benefits and cost savings to justify the costs as long as the effects last into the medium term. The implementation of telemedicine services continues to be limited by cost and reimbursement barriers; future studies should increase transparency and conduct rigorous and in-depth cost-effectiveness analyses of the various types of telemedicine strategies to support T1DM management.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study on the cost-effectiveness of telemedicine interventions, smartphone app, SMS text messaging, and website interventions were confirmed to be cost-effective without substantial differences among the different delivery modes [ 70 ]. A study by Elliott et al [ 71 ] showed that smart wearable devices increase short-term costs but their HbA 1c -lowering benefits will provide sufficient long-term health benefits and cost savings to justify the costs as long as the effects last into the medium term. The implementation of telemedicine services continues to be limited by cost and reimbursement barriers; future studies should increase transparency and conduct rigorous and in-depth cost-effectiveness analyses of the various types of telemedicine strategies to support T1DM management.…”
Section: Discussionmentioning
confidence: 99%